Usefulness of clinical data and rapid diagnostic tests to identify bacterial etiology in adult respiratory infections - Pilar Toledano-Sierra (Medwave, 2015)
Respiratory tract infections are a common complaint and most of them, such as common cold and laryngitis, are viral in origin, so antibiotic use should be exceptional. However, there are other respiratory tract infections (sinusitis, pharyngitis, lower respiratory tract infections, and exacerbations of chronic obstructive pulmonary disease) where a bacterial etiology is responsible for a non-negligible percentage, and antibiotics are often empirically indicated. The aim of the study is to identify the strength of the data obtained from the symptoms, physical examination and rapid diagnostic methods in respiratory infections in which antibiotic use is frequently proposed in order to improve diagnosis and influence the decision to prescribe these drugs. The review concludes that history, physical examination and rapid tests are useful to guide the need for antibiotic treatment in diseases such as acute sinusitis, acute pharyngitis, exacerbation of lower respiratory tract infection and chronic obstructive pulmonary disease. However, no isolated data is accurate enough by itself to confirm or rule out the need for antibiotics. Therefore, clinical prediction rules bring together history and physical examination, thereby improving the accuracy of the decision to indicate or not antibiotics.